2016
DOI: 10.7717/peerj.2081
|View full text |Cite
|
Sign up to set email alerts
|

ABC transporters P-gp and Bcrp do not limit the brain uptake of the novel antipsychotic and anticonvulsant drug cannabidiol in mice

Abstract: Cannabidiol (CBD) is currently being investigated as a novel therapeutic for the treatment of CNS disorders like schizophrenia and epilepsy. ABC transporters such as P-glycoprotein (P-gp) and breast cancer resistance protein (Bcrp) mediate pharmacoresistance in these disorders. P-gp and Bcrp are expressed at the blood brain barrier (BBB) and reduce the brain uptake of substrate drugs including various antipsychotics and anticonvulsants. It is therefore important to assess whether CBD is prone to treatment resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 66 publications
(91 reference statements)
3
34
0
Order By: Relevance
“…In humans, polymorphism of phenotypes for the gene Multi-Drug Resistance 1 affects the development of dependence from cannabis. A more thorough investigation could be useful to increase knowledge on discrepancy observed in individual responses to THC effects [94].…”
Section: Cannabinoids and Efflux Pumps In The Blood-brain Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, polymorphism of phenotypes for the gene Multi-Drug Resistance 1 affects the development of dependence from cannabis. A more thorough investigation could be useful to increase knowledge on discrepancy observed in individual responses to THC effects [94].…”
Section: Cannabinoids and Efflux Pumps In The Blood-brain Barriermentioning
confidence: 99%
“…Results of the study showed that CBD plasma concentrations were not higher in P-gp, Bcrp, or P-gp/Bcrp knockout mice compared with wild type mice. Therefore, since it has been suggested that CBD is not a substrate of P-gp or Bcrp and can represent a promising drug to be used for CNS diseases [94]. If we look at CBD as a therapeutic strategy for CNS diseases, and since P-gp or Bcrp do not obstacle the brain entry of CBD, as consequence, CBD may be free from the development of drug resistance when it is played by these ABC transporters.…”
Section: Figurementioning
confidence: 99%
“…It is important to mention that CBD is not a substrate of P‐glycoprotein. In mice, experiments revealed that the overexpression of this transporter at BBB does not limit the brain uptake of CBD . This condition associated with the inhibitory effect of P‐glycoprotein at BBB plus its anticonvulsant and neuroprotective effects suggests that CBD can be an attractive adjunctive therapy to control drug‐resistant epilepsy.…”
Section: Cannabidiol May Act On Unconventional Central and Peripheralmentioning
confidence: 99%
“…In mice, experiments revealed that the overexpression of this transporter at BBB does not limit the brain uptake of CBD. 119 This condition associated with the inhibitory effect of P-glycoprotein at BBB plus its anticonvulsant and neuroprotective effects suggests that CBD can be an attractive adjunctive therapy to control drug-resistant epilepsy. However, further studies are necessary to demonstrate that the exposure to CBD blocks the activity of P-glycoprotein and/or reverts its overexpression in neurons and astrocytes in brain tissue obtained from subjects with drug-resistant epilepsy.…”
Section: On Unconventional Central and Peripheral Targets To Control mentioning
confidence: 99%
“…Polyspecific ABC transporters, including P-glycoprotein (ABCB1), MRP1 (ABCC1), and breast cancer resistance protein (BCRP; ABCG2), are associated with MDR. 4,5 ABCG2 was discovered in the multidrug-resistant breast cancer cell line MCF-7/AdrVp. 6,7 This protein is expressed in various organs with barrier functions and numerous types of cancer.…”
Section: Introductionmentioning
confidence: 99%